Editorial Perspective: The new Special Educational Needs and Disability Code of Practice—an opportunity for school mental health services?. Issue 2 (21st January 2016) - Foreman, David
Abstract: The 2014 English Special Educational Needs and Disability (SEND) Code of Practice, a policy framework for delivery of a range of services including Schools Mental Health Services (SMHS), is considered in the context of international research on the delivery of mental health services in schools. Effective interventions have been reported in poor and middle‐income countries, whereas there is less information about routine services in high‐income societies, and what they report are equivocal outcomes. In England and the United States, problems with acceptability of routine mental health assessment, together with conflict over resource allocation significantly impede both effectiveness and acceptability. The new Code has been specifically written to support better engagement between Education and Mental Health, but piloting suggests that this has not yet happened. Proactive multiagency planning within the framework of the Code, linked to explicit work on organizational transformation, could provide an effective and acceptable Schools Mental Health Service, with legal protection from subsequent deleterious policy and funding changes. Explicit recommendations for using the Code are appended.